Two new species and two detailed chaetotaxy descriptions of Seira (Collembola: Entomobryidae) from Brazil - Godeiro, Nerivânia N.; Bellini, Bruno C. (Zootaxa, 2015)
Two new species, Seira coroatensis sp. nov. and Seira diamantinae sp. nov., from different areas of Caatinga Biome, Northeastern Brazil, are described and illustrated in this paper. Seira coroatensis sp. nov. share some similarities with Seira mendoncae Bellini & Zeppelini and Seira ritae Bellini & Zeppelini, but presents a very distinct pattern of setae on dorsal head and mesothorax. In the other hand, Seira diamantinae sp. nov. is the fifth neotropical species described bearing modified blunt macrosetae on distal manubrium and proximal dens. The detailed dorsal chaetotaxy of S. paraibensis Bellini & Zeppelini and S. glabra Godeiro & Bellini are presented with some notes regarding the original descriptions of the species.